Occurrence of primary lymphocytic hypophysitis in two horses and presence of scattered T-lymphocytes in the normal equine pituitary gland - Grau-Roma, Llorenc; Peckham, Robert; Paton, Jacqui; Stahel, Anina; de Brot, Simone (SAGE, 2017)
The postmortem examination of a 14-year-old Appaloosa gelding with clinically diagnosed pituitary pars intermedia dysfunction showed a unique finding of moderate multifocal lymphocytic hypophysitis (LH). The pituitary glands of 24 horses submitted for postmortem examination were examined grossly and examined histologically for the presence of lymphocytes. Of these 23 horses, 1 additional case suffered from moderate LH. The 2 cases with LH tested negative for Equid herpesvirus 1 and 4 by polymerase chain reaction and immunohistochemistry (IHC), and no viral particles were observed by electron microscopy in 1 case examined. The cause of LH remains unknown, but based on the T-lymphocytic nature of the inflammation and the human literature, an immune-mediated origin is hypothesized. In addition, the review of 24 cases revealed that 10 horses had few and small multifocal lymphocytic infiltrates within the pituitary gland; the remaining 12 horses showed no evident lymphocytes when examined by hematoxylin and eosin. IHC for CD3 showed the presence of a small number of individual T-lymphocytes scattered through the gland in all examined horses, which appears therefore to be a normal feature of the pituitary gland in horses.